STUDI ANALISIS PUTUSAN PENGADILAN AGAMA KLATEN NOMOR 1708/PDT.G/2023/PA.KLT TENTANG CERAI KARENA SYIQOQ - Yulianto, Rahmat; Baehaqi, B; Sulistyowati, S (AL HUKMU: Journal of Islamic Law and Economics, 2025)
The main problem for those seeking justice through the courts is related to the decision of the panel of judges, not a few of them seek justice but instead get injustice or those who are innocent but when processed in court are the ones who are guilty, this is closely related to the process, legal considerations and conformity with religious norms, this research aims to determine the legal considerations and analysis of Islamic family law regarding this decision. This research uses qualitative research methods. The data collection technique uses field research techniques, namely documentation, direct interviews with judges at the Klaten religious court in order to obtain complete data sources and observations. Data analysis uses qualitative analysis, while testing the validity of the data is carried out through credibility, transferability, dependability and confirmability tests. In this research the author describes the court decision regarding Syiqoq divorce. The research and analysis results show that the legal basis used by the panel of judges in deciding cases is article 39 (2) of Law No. 1. As well as following the recommendations of Islamic law, namely Al-Qur'an surah An-Nisa' verse 35 and Al-Baqoroh verse 231, advice to judges to always be fair and adhere to applicable law.